Effects of acupuncture and Nordic walking practice, and their interaction, on bodily fluids distribution of breast cancer survivors - Andrea Di Blasio; Massimo Rinaldi; Teresa Morano; Pascal Izzicupo; Stefania Dell'aquila; Simona Grossi; Luca Russo; Marco Bergamin; Stefano Gobbo; Gianluca Viscioni; David Cruz-Díaz; Francesca Di Giandomenico; et al. (Termedia Publishing House, 2022)
Purpose Integrative treatments are growing among breast cancer survivors (BCS), and both acupuncture and Nordic walking (NW) are found particularly useful for them. Their positive effect on BCS health is partially due to their impact on bodily fluid balance. The study of bodily resistance and reactance is a practical method to monitor bodily fluid balance. The aims of our study were to investigate (a) the acute effects of acupuncture treatment on resistance and reactance in BCS who never had received acupuncture treatment before; (b) if BCS practising NW had better resistance and reactance than non-exercising BCS; and (c) if BCS practising NW presented a better response after acupuncture treatment than other conditions. Methods A total of 80 BCS (53.24 ± 5.50 years), including 38 women not practising physical exercise and 42 Nordic walkers, were recruited and investigated for bodily resistance and reactance immediately before and after (a) acupuncture treatment; (b) supine rest without acupuncture. Results Acupuncture seems to positively influence bodily resistance and reactance variation compared with supine rest. NW practice seems able to assure the best resistance and reactance basal values, and their best positive variation after supine rest and acupuncture alone. The observed results are amplified when NW and acupuncture are coupled. Conclusions Both acupuncture and NW could be used to positively influence bodily fluids distribution, also considering that, when coupled, their positive effects are amplified. Therefore, NW should be prescribed to maintain the positive effect of acupuncture or to prepare the body for it.